Functional significance of ion channels during macropinosome resolution in immune cells - Maekawa, Masashi; Natsume, Ren; Arita, Makoto (Frontiers in Physiology, 2022)
Macropinocytosis is a unique type of endocytosis accompanied by membrane ruffle formation. Closure of membrane ruffles leads to the uptake of large volumes of fluid phase and, subsequently, the formation of large vacuoles termed macropinosomes. Immune cells, such as dendritic cells, T cells, and macrophages, endocytose the surrounding amino acids and pathogens via macropinocytosis either constitutively or in a stimulus-dependent fashion. This process is critical for cell migration, mammalian target of rapamycin complex 1 (mTORC1) activation, and antigen presentation. Large vacuoles are fragmented into tubules and smaller vesicles during the progression and maturation of macropinosomes in immune cells. This process is called “macropinosome resolution” and requires osmotically driven shrinkage of macropinosomes, which is controlled by ion channels present in them. The crenation of membranes on shrunken macropinosomes is recognized by curvature-sensing proteins and results in intracellular membrane trafficking. In this mini review, we highlight the recent progress in research on macropinosome resolution in macrophages, with a focus on ion channels (TPC1/2 for Na+ and TMEM206 for Cl-) that is required for macropinosome resolution. We also discuss the potential contribution of membrane lipids to this process.